Clinical Practice Guidelines Using GRADE and AGREE II for the Impact of Genetic Variants on Plasma Lipid/Lipoprotein/Apolipoprotein Responsiveness to Omega-3 Fatty Acids - Keathley, Justine; Garneau, Véronique; Marcil, Valérie; Mutch, David M.; Robitaille, Julie; Rudkowska, Iwona; Sofian, Gabriela; Desroches, Sophie; Vohl, Marie-Claude (Frontiers in Nutrition, 2022)
A recent systematic review, which used the GRADE methodology, concluded that there is strong evidence for two gene-diet associations related to omega-3 and plasma triglyceride (TG) responses. Systematic reviews can be used to inform the development of clinical practice guidelines (CPGs). To provide guidance for clinical practice related to genetic testing for predicting responsiveness to dietary/supplemental omega-3s and their impact on plasma lipids/lipoproteins/apolipoproteins. Using the results of the abovementioned systematic review, the first CPGs in nutrigenetics were developed using the established GRADE methodology and AGREE II approach. Three clinical practice recommendations were developed. Most gene-diet associations identified in the literature lack adequate scientific and clinical validity to warrant consideration for implementing in a practice setting. However, two gene-diet associations with strong evidence (GRADE quality: moderate and high) can be considered for implementation into clinical practice in certain cases: male APOE-E4 carriers (rs429358, rs7412) and TG changes in response to the omega-3 fatty acids eicosapentaenoic acid (EPA) and/or docosahexaenoic acid (DHA) as well as a 31-SNP nutrigenetic risk score and TG changes in response to EPA+DHA among adults with overweight/obesity. Ethical and regulatory implications must be considered when providing APOE nutrigenetic tests given the well-established link between APOE genetic variation and Alzheimer’s Disease. Most of the evidence in this area is not ready for implementation into clinical practice primarily due to low scientific validity (quality of evidence). However, the first CPGs in nutrigenetics have been developed for two nutrigenetic associations with strong scientific validity, related to dietary/supplemental omega-3 and TG responses.